2019
DOI: 10.1016/j.pocean.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of large gadiforms in the food web of a continental shelf ecosystem

Abstract: Human activities affect continental shelves, especially due to the harvest of living marine resources. Understanding their functioning and dynamics has become a growing concern in recent decades, especially through use of trophic modelling approaches. Studying the feeding ecology of key component species also improves this understanding by providing accurate information on trophic processes, particularly the dependence on trophic pathways. This study focuses on the trophic ecology of four large gadiforms (cod,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…The predominance of pelagic production as the main source of organic matter is consistent with previous empirical and modelling studies (Bănaru et al, 2013;Day et al, 2019;Lassalle et al, 2011). Pelagic production can notably enter food webs after sedimentation, through the use of detrital matter of pelagic origin.…”
Section: Resultssupporting
confidence: 89%
“…The predominance of pelagic production as the main source of organic matter is consistent with previous empirical and modelling studies (Bănaru et al, 2013;Day et al, 2019;Lassalle et al, 2011). Pelagic production can notably enter food webs after sedimentation, through the use of detrital matter of pelagic origin.…”
Section: Resultssupporting
confidence: 89%
“…In the Celtic Sea ecosystem, higher specialization among generalist species feeding in different microhabitats may therefore provide opportunities to maximize resource use (i.e., niche complementarity) and thus augment productivity. Indeed, Day et al (2019) found distinct feeding niches and strategies within four dominant predatory fishes, which effectively limit interspecific competition in the area. Consistent with the results obtained for the other metrics, low isotopic dispersion showed average trophic diversity in the food web is low due to substantial reductions in the abundance of top predator fish due to intense fishing in the area, which has cascaded into an increased abundance of small, pelagic and demersal fishes feeding lower in the food web over time (Pinnegar et al 2002; Hernvann and Gascuel 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We used the widely distributed great scallop ( P. maximus ; Supporting Information Fig. S1) to provide a realistic trophic baseline estimate for the majority of taxa in this study, which we expect to rely upon a mixture of both benthic and pelagic food sources (Rault et al 2017; Kopp et al 2018; Day et al 2019). Following the studies of Barnes et al (2009) and Jennings and van der Molen (2015) conducted in the same ecosystem, invertebrate and fish δ 13 C and δ 15 N were corrected for spatial variation in the isotopic baseline based on environmental data as follows: δ13Cbase,i=0.322Ti20.347 δ15Nbase,i=b0+b1Ti+b2Si+b3Smin,i+b4TiSi+ɛi where δ 13 C base, i and δ 15 N base, i are the corrected baseline δ 13 C and δ 15 N values, respectively, for the individual i , T , and S are annual mean bottom temperature and salinity, respectively, S min is minimum monthly salinity, and b 0 , b 1 , b 2 , b 3 , b 4 are the fit statistics used to simulate uncertainty in δ 15 N base (Jennings and van der Molen 2015).…”
Section: Methodsmentioning
confidence: 99%
“…EcoDiet allows to simultaneously estimate diet proportions of all functional groups by integrating multiple data types, i.e., stomach content analyses, biotracer analyses and literature knowledge. Here, EcoDiet was applied to trophic analyses conducted on fish collected in the Celtic Sea during a fisheries-independent survey as part of the EATME project (Issac et al, 2017;Rault et al, 2017;Day et al, 2019), and information from an updated bibliographic search. The new model comprised a total of 50 single and multispecies functional groups, including exploited fishes and invertebrates, non-commercial benthic invertebrates (five groups), zoo-and phyto-plankton (four and two groups, respectively), and mammals and seabirds (four groups).…”
Section: Updating and Improving The Pre-existing Celtic Sea Ecopath Mmentioning
confidence: 99%
“…Some of these functional groups were further split into younger and older life-stage groups (cod Gadus morhua, hake Merluccius merluccius, and anglerfish Lophius sp.) based on onthogenetic changes in diet identified by stomach content analyses (Issac et al, 2017;Day et al, 2019). Details on the Celtic Sea Ecopath model, its parameters, and the species it represents can be found in Supplementary Appendix SB.…”
Section: Updating and Improving The Pre-existing Celtic Sea Ecopath Mmentioning
confidence: 99%